Respuesta :

Answer:

x=-3

|-x| = 3

|x| = 3

Step-by-step explanation:

we know that

If a number is a solution of a equation, then the number must satisfy the equation

Verify each case

case 1) we have

x=3

substitute the value of x=-3

-3=3 -----> is not true

therefore

x=-3 is not a solution of the given equation

case 2) we have

x=-3

substitute the value of x=-3

-3=-3 -----> is true

therefore

x=-3 is  a solution of the given equation

case 3) we have

|-x| = 3

substitute the value of x=-3

|-(-3)| = 3

|3| = 3

3=3-----> is true

therefore

x=-3 is a solution of the given equation

case 4) we have

|x| = 3

substitute the value of x=-3

|(-3)| = 3

3=3-----> is true

therefore

x=-3 is a solution of the given equation

case 5) we have

-|x| = 3

substitute the value of x=-3

-|(-3)| = 3

-3=3-----> is not true

therefore

x=-3 is not a solution of the given equation